Diagnostic Evaluation of the IS1081-Targeted Real-Time PCR for Detection of Mycobacterium bovis DNA in Bovine Milk Samples - Mohamed M. Zeineldin; Kimberly Lehman; Patrick Camp; David Farrell; Tyler C. Thacker (Pathogens, 2023)
The ability of Mycobacterium bovis (M. bovis) to survive in bovine milk has emerged as a serious public health concern. The first objective of this study was to evaluate the diagnostic utility of IS1081-targeted real-time PCR for the detection of M. bovis DNA in different fractions of bovine milk. In a model study, bovine milk samples were spiked with serially diluted M. bovis BCG to investigate the detection limit of M. bovis DNA in whole milk and milk fractions (cream, pellet, and pellet + cream combined) using IS1081 real-time PCR. The assay was then used to detect M. bovis DNA in whole milk and milk fractions from naturally infected animals. The results showed that the IS1081 real-time PCR was more sensitive when detecting M. bovis DNA in the cream layer alone and cream + pellet combined compared to whole milk or the pellet alone. While PCR-based diagnostic assays for the detection of M. bovis in milk samples provide a quicker diagnostic tool for bovine tuberculosis, safe processing, and handling of M. bovis-infected milk samples remain a challenge and pose a human health risk. PrimeStore Molecular Transport Medium (MTM) has been shown to rapidly inactivate infected specimens while preserving nucleic acid for subsequent Molecular analysis. Therefore, the secondary objective of this study was to evaluate the ability of MTM to inactivate M. bovis BCG in spiked milk samples as well as its ability to preserve BCG DNA for the PCR assay. The results showed that MTM can successfully inactivate BCG alone or in spiked milk samples while preserving DNA for the PCR assay. The CT values of M. bovis BCG alone and spiked milk samples aliquoted in MTM and without MTM were similar at various dilutions. Taken together, our results indicate that using DNA extracted from the milk cream fraction alone or combined milk cream and pellet improved the recovery rate of M. bovis DNA in bovine milk samples. MTM has the potential to provide a safe and rapid sample processing tool for M. bovis inactivation in milk samples and preserve DNA for molecular diagnostics.